2010
DOI: 10.1159/000253849
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Dysfunction in Japanese Patients with Gastroesophageal Reflux Disease: Prevalence, Risk Factors, and Efficacy of Rabeprazole

Abstract: Background and Aim: Several studies performed in Western countries demonstrate the association between sleep dysfunction and gastroesophageal reflux disease (GERD), especially when nighttime heartburn is present. The purpose of this study was to examine the prevalence and risk factors of sleep dysfunction, and the effect of rabeprazole on reflux symptoms and sleep dysfunction in Japanese GERD patients. Methods: A total of 134 GERD patients, including 82 patients with non-erosive reflux disease (NERD), were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 46 publications
3
36
1
Order By: Relevance
“…In the present study, the relationships between sleep disturbances and various abdominal symptoms were evaluated in subjects without organic gastrointestinal disease. Our results showed that GERD-like symptoms, such as heartburn and acid regurgitation, aggravate daytime sleepiness, as previously reported (3)(4)(5)13). However, the presence of GERDlike symptoms was not found to have a statistically significant effect on the incidence of sleep disturbances (ESS score !…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the present study, the relationships between sleep disturbances and various abdominal symptoms were evaluated in subjects without organic gastrointestinal disease. Our results showed that GERD-like symptoms, such as heartburn and acid regurgitation, aggravate daytime sleepiness, as previously reported (3)(4)(5)13). However, the presence of GERDlike symptoms was not found to have a statistically significant effect on the incidence of sleep disturbances (ESS score !…”
Section: Discussionsupporting
confidence: 85%
“…and it may be disturbed by gastrointestinal symptoms. Reflux symptoms, including heartburn and acid regurgitation, that occur during the nocturnal period have been repeatedly reported to impair sleep quality (3)(4)(5)(6), and GERD is regarded to be a disease with nocturnal symptoms that must be completely eliminated in order to relieve sleep disturbances (13). In the present study, the relationships between sleep disturbances and various abdominal symptoms were evaluated in subjects without organic gastrointestinal disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Fujiwara et al examined the effects of rabeprazole at a dose of 10 mg for eight weeks on sleep disturbances in 134 patients with GERD who subsequently completed the PSQI. The authors found that 52% of the patients with GERD had sleep disturbances and that PPI treatment significantly improved the PSQI scores (6). Another study showed that twice daily treatment with rabeprazole for four to eight weeks significantly reduced the frequency of nighttime reflux symptoms, arousals due to nighttime reflux symptoms during sleep, daytime sleepiness and poor sleep quality in patients refractory to once daily standard PPI treatment (26).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of GERD treatment is to al-with non-erosive reflux disease are highly affected by sleep disturbances in Japan (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%